دور إدارة الوقت في تحسين أداء إدارة الإمداد في المؤسسات الصناعية - دراسة ميدانية لعينة من المؤسسات الصناعية في ولاية الوادي- - حسين عبابه; جمال الدين بن عوده; حسين نوري (جامعة الوادي University Of Eloued, 2024)
هدفت هذه الدراسة إلى التعرف على دور إدارة الوقت في تحسين أداء إدارة الإمداد، واختبار إمكانية وجود تأثير لإدارة الوقت على تحسين أداء إدارة الإمداد, وذلك من خلال دراسة ميدانية على مجموعة من المؤسسات الصناعية بولاية الوادي، واعتمدنا على المنهج الوصفي في الجانب النظري, والمنهج الاحصائي في الجانب التطبيقي, ولتحقيق أهداف الدراسة تم إعداد وتصميم استمارة وزعت على المسؤولين التنفيذيين لأقسام (الشراء, التخزين, الإنتاج, التوزيع) بتلك المؤسسات, وقد اعتمدنا في تحليل بيانات الاستبيان على برنامج الحزمة الإحصائية للعلوم الاجتماعية SPSS إصدار 26, برنامج معالج الجداول Excel إصدار 2023. وفي الأخير خلصت الدراسة إلى مجموعة من النتائج أهمها ظهور أهمية إدارة الوقت بوظيفتي الشراء والإنتاج من خلال التخطيط, التنظيم والرقابة؛ كما أهملت أهمية إدارة الوقت بوظيفتي التخزين والتوزيع؛ واقتصر دور التخطيط للوقت على وظيفة الانتاج فقط؛ كما اقتصر دور الرقابة للوقت في إدارة الشراء فقط. This study aimed to identify the role of time management in improving the performance of supply management, and to test the possibility of an impact of time management on improving the performance of supply management, through a field study on a group of industrial institutions in the state of Al-Wadi, and we relied on the descriptive approach in the theoretical aspect, and the method The statistician is on the applied side, and to achieve the objectives of the study, a questionnaire was prepared and designed and distributed to the executive officials of the departments (purchasing, storage, production, distribution) of these institutions. We relied in analyzing the questionnaire data on the Statistical Package for the Social Sciences (SPSS) program, version 26, and the Excel spreadsheet processor program, version 26. 2023. Finally, the study concluded with a set of results, the most important of which is the emergence of the importance of time management in the functions of purchasing and production through planning, organization and control. It also neglected the importance of time management in the storage and distribution functions. The role of time planning was limited to the production function only. The role of time control was limited to purchasing management only.
مذكرة ماستر
Keywords: الوقت، إدارة الوقت، تحسين الأداء، الإمداد; إدارة الإمداد.; time; time management; performance improvement; supply; supply management.